2021
DOI: 10.1021/acssuschemeng.0c06224
|View full text |Cite
|
Sign up to set email alerts
|

Two in One: Poly(ethyleneimine)-Modified MnO2 Nanosheets for Ultrasensitive Detection and Catalytic Reduction of 2,4,6-Trinitrotoluene and Other Nitro Aromatics

Abstract: The development of a portable sensor for on-site sensing of 2, 4, 6-trinitrotoluene (TNT) and other nitro aromatics (NAs) is still needed to strengthen environmental protection and public security. Herein, we report the fabrication of fluorescent few-layered MnO 2 nanosheets (FL-MnO 2 NSs) via N,N-dimethyl formamide-mediated ultrasonication and hydrothermal treatment. Electron and spectroscopy studies demonstrate that the modification of the FL-MnO 2 NSs (named as PEI-FL-MnO 2 NSs) with amine-rich polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Previous studies in the literature have shown that, usually, the positions of band edges for CeO 2 use Mott–Schottky plots and obtain UV-Vis DRS results. The Mott–Schottky plots of Ce showed positive slopes, and 600 Ce-SPC was an n-type semiconductor [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in the literature have shown that, usually, the positions of band edges for CeO 2 use Mott–Schottky plots and obtain UV-Vis DRS results. The Mott–Schottky plots of Ce showed positive slopes, and 600 Ce-SPC was an n-type semiconductor [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…After heating to boiling for 15 min, sodium citrate (38.8 mM, 1 mL) was immediately injected into the heated solution. The resulting solution was then heated under continuous stirring for 20 min before being cooled to room temperature . The obtained wine-red solution exhibited surface Plasmon resonance absorption at 518 nm, indicating that the size of the formed C-AuNPs was approximately 13 ± 1 nm (Figure I).…”
Section: Methodsmentioning
confidence: 99%
“…We transferred HAuCl 4 (1 M, 100 L) to 100 mL of Milli-Q water in a round-bottom flask and heated the solution for 15 min, and then sodium citrate (0.8 mL, 38.8 mM) was added immediately. The obtained mixture was further heated for another 20 min under continuous stirring . The final product was prepared by baking the C-AuNPs (dark burgundy color) at 80 °C for further application.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations